DEVELOPING AN INCLUSIVE APPROACH TO TEACHING ENGLISH AS A MAJOR TO VIETNAMESE VISUALLY-IMPAIRED STUDENTS AT ULIS, VNU, HANOI - Anh, Nguyen Tuan (VNU Journal of Foreign Studies, 2020)
Teritary inclusive education has become more and more popular in the world in different fields of education and training, and ULIS is one of the few foreign-language-specialized universities in Vietnam that have visually-impaired students persuing one of its undergraduate degrees. Through an analysis of the study diary by one of the new visually-impaired graduates at ULIS and a direct interview via telephone, this study focuses on investiating all the elements involved in the making of “a speacial product” and aims to propose a model process of training visually-impaired students at the tertiary level. The results, to a large extent, show a high applicability of the model, provided that interested universities are “really serious” and wish to open the door of opportunities to visually-impaired students.